2014
DOI: 10.18632/oncotarget.1875
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic plasticity: A central regulator of epithelial-to-mesenchymal transition in cancer

Abstract: Tumor metastasis is the major cause of mortality and morbidity in most solid cancers. A growing body of evidence suggests that the epithelial-to-mesenchymal transition (EMT) plays a central role during tumor metastasis and frequently imparts a stem cell-like phenotype and therapeutic resistance to tumor cells. The induction of EMT is accompanied by a dynamic reprogramming of the epigenome involving changes in DNA methylation and several post-translational histone modifications. These changes in turn promote th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 131 publications
(132 reference statements)
2
93
0
Order By: Relevance
“…Certain chromatin complexes are involved in the post-translational modification (e.g., methylation, acetylation, ubiquitylation) of histones, leading to activation or suppression of transcription of specific genes [57,58]. The methylation of nucleosomal histones at specific lysine residues can either repress (e.g., H3K9me3, H3K27me3) or stimulate (e.g., H3K4me3) transcription.…”
Section: Regulation Of Gene Expression In Stromal Cells By Histone Momentioning
confidence: 99%
See 1 more Smart Citation
“…Certain chromatin complexes are involved in the post-translational modification (e.g., methylation, acetylation, ubiquitylation) of histones, leading to activation or suppression of transcription of specific genes [57,58]. The methylation of nucleosomal histones at specific lysine residues can either repress (e.g., H3K9me3, H3K27me3) or stimulate (e.g., H3K4me3) transcription.…”
Section: Regulation Of Gene Expression In Stromal Cells By Histone Momentioning
confidence: 99%
“…Histone demethylases, which remove methyl groups from histones, also play active roles in regulating the epigenetic status of the cell [61]. Histone acetylation at specific lysines (e.g., H3K9, H3K36, H3K27) is accomplished by a large group of histone acetylases and is often associated with gene activation, whereas removal of these acetyl marks by histone deacetylases (HDACs) is linked to gene repression [57,[62][63].…”
Section: Regulation Of Gene Expression In Stromal Cells By Histone Momentioning
confidence: 99%
“…The methylation of CpG islands in gene promoters has been strongly linked to the silencing of the expression of tumor-suppressor genes in different types of cancers (14)(15)(16)(17). The hypermethylation of promoter CpG islands has been found to affect not only tumor-suppressor mRNAs, but also tumor-suppressor miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Together we seek to detect whether there exists any functional association (Szklarczyk et al, 2015) between those identified genes from hyper-DMRs and hypo-DMRs, which can explain the differential expression between those genes qualitatively, especially for the genes belonging to tumor suppressor genes (TSG) (Bedi et al, 2014;Blattler et al, 2014;Zhao et al, 2013). …”
Section: Visualization and Function Analysis For The Annotation Resultsmentioning
confidence: 99%